1973
DOI: 10.1159/000180181
|View full text |Cite
|
Sign up to set email alerts
|

The Hormonal and Non-Hormonal Control of Renal Excretion of Calcium and Magnesium

Abstract: This report reviews the various hormonal and non-hormonal factors involving the renal handling of calcium and magnesium and the effect of these factors on the relationship between the excretions of these divalent ions and that of sodium. Among the factors discussed are: (1) extracellular volume expansion, (2) renal vasodilatation, (3) changes in glomerular filtration rate, Parathyroid hormone (4) hypercalcemia and hypermagnesemia, (5) diuretics, (6) phosphate depletion and loading, (7) alterations in acid base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2
6

Year Published

1977
1977
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(38 citation statements)
references
References 158 publications
(235 reference statements)
2
28
2
6
Order By: Relevance
“…Previous immunohistochemical studies in mouse kidney indeed indicated that TRPM6 is localized exclusively along the apical domain in DCT, which is in line with the postulated gatekeeper function in the process of active Mg 2ϩ reabsorption (13 excretion without significant increases in plasma Mg 2ϩ , which is in accordance with the results of our study in mouse (27 increased urinary Ca 2ϩ excretion. In accordance with this finding, Shafik and Quamme (7) showed that urinary Ca 2ϩ excretion decreases in rats that are maintained on a low-Mg 2ϩ diet.…”
Section: Discussionsupporting
confidence: 92%
“…Previous immunohistochemical studies in mouse kidney indeed indicated that TRPM6 is localized exclusively along the apical domain in DCT, which is in line with the postulated gatekeeper function in the process of active Mg 2ϩ reabsorption (13 excretion without significant increases in plasma Mg 2ϩ , which is in accordance with the results of our study in mouse (27 increased urinary Ca 2ϩ excretion. In accordance with this finding, Shafik and Quamme (7) showed that urinary Ca 2ϩ excretion decreases in rats that are maintained on a low-Mg 2ϩ diet.…”
Section: Discussionsupporting
confidence: 92%
“…This response is rapid, occurring within 4-8 hours; is sensitive, proceeds without a detectable change in plasma magnesium concentration; and is selective in the long term, altering magnesium reabsorption without changes in Na + or Ca 2+ excretion. Conversely in states of magnesium surfeit, urinary magnesium markedly increases without significant increases in plasma magnesium (101). This ability to adapt to magnesium availability is intrinsic as it may be observed in isolated cells independent of hormones and other factors (60, 61).…”
Section: Intrinsic Control: Magnesium Restrictionmentioning
confidence: 99%
“…The Ca 2+ /Mg 2+ -sensing receptor also explains the so-called "Tm" phenomenon of urinary magnesium excretion (101,(120)(121)(122). Clearance studies have suggested that renal magnesium reabsorption is a Tmlimited process, i.e.…”
Section: 2ca2+/mg2+-sensing:hypercalcemia Hypermagnesemiamentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies also, bladder tumours occurred preferentially in male rats fed high levels of saccharin (Taylor & Friedman, 1974;Tisdel et al, 1974;Arnold et al, 1979) but there was no consistent relationship between urolithiasis and bladder tumours. Discrepancies in urolithiasis between different studies could reflect variation in dietary cation, carbohydrate or protein content, all of which may affect urine composition (Andersen, 1962;Lyon et al, 1966;Woodard, 1971;Massry & Coburn, 1973). The urolithiasis associated with our 3 bladder tumours consisted of free-lying calculi and/or mineralized deposits adherent to or within the tumours.…”
Section: Discussionmentioning
confidence: 90%